ILC2 require cell-intrinsic ST2 signals to promote type 2 immune responses - Topczewska, Patrycja M.; Rompe, Zoe A.; Jakob, Manuel O.; Stamm, Anton; Leclère, Pierre S.; Preußer, Alexandra; Duerr, Claudia U.; Thole, Linda Marie Laura; Kotsch, Katja; Artis, David; Klose, Christoph S. N. (Frontiers in Immunology, 2023)
The initiation of type 2 immune responses at mucosal barriers is regulated by rapidly secreted cytokines called alarmins. The alarmins IL-33, IL-25 and TSLP are mainly secreted by stromal and epithelial cells in tissues and were linked to chronic inflammatory diseases, such as allergic lung inflammation, or to resistance against worm infections. Receptors for alarmins are expressed by a variety of immune cells, including group 2 innate lymphoid cells (ILC2s), an early source of the type 2 cytokines, such as IL-5 and IL-13, which have been linked to atopic diseases and anti-worm immunity as well. However, the precise contribution of the IL-33 receptor signals for ILC2 activation still needs to be completed due to limitations in targeting genes in ILC2. Using the newly established Nmur1iCre-eGFP mouse model, we obtained specific conditional genetic ablation of the IL-33 receptor subunit ST2 in ILC2s. ST2-deficient ILC2s were unresponsive to IL-33 but not to stimulation with the alarmin IL-25. As a result of defective ST2 signals, ILC2s produced limited amounts of IL-5 and IL-13 and failed to support eosinophil homeostasis. Further, ST2-deficient ILC2s were unable to expand and promote the recruitment of eosinophils during allergic lung inflammation provoked by papain administration. During infection with Nippostrongylus brasiliensis, ILC2-intrinsic ST2 signals were required to mount an effective type 2 immune response against the parasite leading to higher susceptibility against worm infection in conditional knockout mice. Therefore, this study argues for a non-redundant role of cell-intrinsic ST2 signals triggering proper activation of ILC2 for initiation of type 2 immunity.